Criminal Justice Drug Abuse Treatment Studies (CJ-DATS): Step 'N Out, 2002-2006 (United States) - Friedmann, Peter ([Verlag nicht ermittelbar], 2011)
Step 'N Out is a research study designed to examine the potential of a new approach to address the re-entry needs of offenders who have substance abuse issues, one which integrates the systems of supervision and treatment. The study is a randomized clinical trial which enrolls subjects who are new to supervision. Those who are in the treatment arm of the study meet with their probation officer weekly for 12 weeks, with every other meeting including a treatment counselor. The PO and counselor have been trained to use motivational interviewing and collaborative behavioral techniques to explore the client's personal issues and triggers that may hamper his/her successful re-entry into the community. The probation officer and counselor work with the client to establish weekly recovery and social goals in the form of a written contract that enables the client to take responsibility for their own actions and decisions. In addition, the variables in this study generally cover topics on drug use and testing; demographics and criminal background; treatment programs and sessions; and finally, relationships between clients and their parole/probation officers.